2023
DOI: 10.1038/s41893-023-01157-x
|View full text |Cite
|
Sign up to set email alerts
|

Earlier collapse of Anthropocene ecosystems driven by multiple faster and noisier drivers

Abstract: A major concern for the world’s ecosystems is the possibility of collapse, where landscapes and the societies they support change abruptly. Accelerating stress levels, increasing frequencies of extreme events and strengthening intersystem connections suggest that conventional modelling approaches based on incremental changes in a single stress may provide poor estimates of the impact of climate and human activities on ecosystems. We conduct experiments on four models that simulate abrupt changes in the Chilika… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
23
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 60 publications
1
23
1
1
Order By: Relevance
“…Our analysis found climate-driven mortality can drive shifts to algal domination even when in a moderately weakened state (i.e., nutrients and fishing are moderately high; Figure 2A ii) that would not be expected based on the deterministic skeleton. This novel theoretical result is related to recent theoretical literature on long transients (Hastings and others 2018, 2021), and importantly highlights the potential for unexpected results when considering noise in our mathematical models (Willcock and others 2023). Furthermore, our theoretical results are grounded in the geometry of our model and thus are highly general.…”
Section: Discussionsupporting
confidence: 77%
“…Our analysis found climate-driven mortality can drive shifts to algal domination even when in a moderately weakened state (i.e., nutrients and fishing are moderately high; Figure 2A ii) that would not be expected based on the deterministic skeleton. This novel theoretical result is related to recent theoretical literature on long transients (Hastings and others 2018, 2021), and importantly highlights the potential for unexpected results when considering noise in our mathematical models (Willcock and others 2023). Furthermore, our theoretical results are grounded in the geometry of our model and thus are highly general.…”
Section: Discussionsupporting
confidence: 77%
“…Due to the small spatial scales and long timescales of oceanic motion, the detection and monitoring of abrupt ocean state changes through observations remains a challenge. Studies have revealed that interactions and combinations of processes and forcings require a downward correction of forcing thresholds for critical changes in Earth system elements (Lade et al., 2020; Steinacher et al., 2013; Willcock et al., 2023). Our study shows that the rising occurrence of abrupt regional ocean state changes due to single forcings call for a further downward adjustment of these thresholds.…”
Section: Discussionmentioning
confidence: 99%
“…Intensification of land use, invasive species and pollution are driving both extinction and extirpation, altering the composition of local communities at an alarming rate [14,15]. Anthropogenic climate change is also shifting the ranges of species [16], and has the potential to significantly impact the geographical distribution of biomes in the near future [7], including risks of abrupt shifts [17]. These vegetation transitions will result in feedback through changed land cover, probably contributing to additional climate warming [18][19][20].…”
Section: Introductionmentioning
confidence: 99%